Impact of Early Childhood School Intervention on Enrollment and Learning Outcomes: Evaluation of a Public Program in India - Nilanjan Bhattacharya; Debayan Pakrashi; Sarani Saha; Soham Sahoo (Institute of Labor Economics (IZA), 2023)
We evaluate the impact of introducing a pre-primary schooling program in government schools in the Indian state of West Bengal in 2013 on children's early enrolment in schools and subsequent test scores. Using double difference, triple difference, and synthetic control methodologies, we find that the program significantly increased enrolment in the pre-primary sections of the government schools. However, the rise in enrolment did not translate into improved performance of the students. Analyzing the test scores, we find that after the program's introduction, both math and reading scores of treated children did not improve compared to the control group. We attribute this result to the deteriorating physical and learning infrastructure in the state government schools, captured via a decline in the availability of classrooms and teachers.
Keywords: I21; I25; I28; 330; pre-primary education; learning outcomes; enrollment